Three Novel Heterozygous Point Mutations of NR3C1 Causing Glucocorticoid Resistance. Issue 8 (11th May 2016) - Vitellius, Géraldine; Fagart, Jérôme; Delemer, Brigitte; Amazit, Larbi; Ramos, Nelly; Bouligand, Jérôme; Le Billan, Florian; Castinetti, Frédéric; Guiochon‐Mantel, Anne; Trabado, Séverine; Lombès, Marc
Abstract : We described three novel heterozygous mutations in NR3C1 gene causing glucocorticoid resistance. p.R477S and p.Y478C are located in the DNA binding domain (DBD) of the glucocorticoid receptor (GR) while p.L67P is located in the ligand binding domain (LBD) of GR. Functional characterization of GR mutants have been investigated and the deleterious consequences on GR signaling have been examined. ABSTRACT: Generalized glucocorticoid resistance is associated with glucocorticoid receptor (GR; NR3C1 ) mutations. Three novel heterozygous missense NR3C1 mutations (R477S, Y478C, and L672P) were identified in patients presenting with adrenal incidentalomas, glucocorticoid excess without Cushing syndrome. Dexamethasone (DXM) binding studies demonstrated that the affinity of GRR477S and GRY478C mutants, located in the DNA‐binding domain (DBD) of GR, was similar to wild‐type GR ( K d = 2–3 nM). In contrast, GRL672P mutant, located in the ligand‐binding domain (LBD) of GR, was unable to bind glucocorticoids and was more sensitive to protein degradation. GR subcellular distribution revealed a marked decrease in DXM‐induced nuclear translocation of GRR477S and GRY478C mutants, whereas GRL672P remained exclusively cytoplasmic. Chromatin immunoprecipitation demonstrated impaired recruitment of DBD mutants onto the regulatory sequence of FKBP5 . Transactivation assays disclosed the lack of transcriptional activity of GRR477S and GRL672P, whereas GRY478C had a reduced transactivation capacity. Three‐dimensional modeling indicated that R477S lost two essential hydrogen bonds with DNA, Y478C resulted in altered interaction with surrounding amino‐acids, destabilizing DBD, whereas L672P altered the H8 helix folding, leading to unstructured LBD. This study identifies novel NR3C1 mutations with their molecular consequences on altered GR signaling and suggests that genetic screening of NR3C1 should be conducted in patients with subclinical hypercorticism.